Balkan Sufism – a perspective of dialogue or confrontation - Hauziński, Jerzy (Balcanica Posnaniensia. Acta et studia, 2009)
Sufism, one of the most complex and multifaceted aspects of Islam, has found its special place in the history of the Balkan Peninsula. It was brought there with the expansion of the Ottoman Empire. The process of Islamisation, largely based on the activities of dervish brotherhoods and tarikats, was not limited to confrontation, but often took the form of peaceful acculturation. The aim of the article is to show the specificity of the development of Sufism in the Balkans and to analyse its role as a tool for intercultural dialogue and potential conflicts. Particular attention is paid to the links between Sufism and the processes of Islamisation, its relations with local Christian and Gnostic communities, and its evolution in the modern and contemporary eras. The analyses are based on historical studies, including accounts by Ottoman chroniclers and travellers (e.g. Evliya Çelebi), research by contemporary Islamic scholars, and texts by mystics. The research method is based on a comparative analysis of religious and institutional traditions, as well as on an interpretation of the literary and social impact of Sufism in the Balkan context. The conclusions indicate that Sufism, although sometimes marginalised as a heterodox movement, played a key role in the Islamisation of the region, particularly thanks to its openness to elements of local culture and spirituality. Over time, it has become a factor shaping national identity (especially in Albania) and cultural synthesis in the Balkans.